INOVASI PELAYANAN PUBLIK MELALUI APLIKASI POEDAK (PELAYANAN ONLINE PENDAFTARAN ADMINISITRASI KEPENDUDUKAN) DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN GRESIK - Dwi Febi Kartika; Trenda Aktiva Oktariyanda (Universitas Negeri Surabaya, 2022)
The government, devoting to both the state and society, is obliged to accommodate prime public service. An example of a governmental agency with an e-government basis service is the Civil Registry Office (Disdukcapil) of Gresik Regency through a website application named Civil Registration Online Service (Poedak). This application is a result of complaints by people on the inconvenience in the civil administration service during COVID-19. This study aims to describe the civil administration service in Gresik Regency’s Disdukcapil through Poedak. It employed descriptive research with a qualitative approach, collected data by interviews, observations, documentation, and literature review. Research focus analysis refers to the success factors of an innovation in the public sector from 6 (six) diagnostic indicators in governance and innovation; source of ideas for innovation; cultural innovation; capabilities and tools; goals, outcomes, drivers, barriers; and collect single information data. The findings show that the system or policy applied aptly meets the regulated procedure, according to the control system and innovation indicators. The innovative ideas are obtained from both internal and external organizations. In this case, the innovation is to ease the civil registration service through a one-gate integrated service system. The innovative equipment and skills will perform functionally well along with Technical Guidance (Bimtek) programs for the civil officers. While the goal indicator for Poedak is the congenial access to the civil registration and administration service, the challenge is that the Poedak application and its assistance in the online civil administration process are still barely known among people.